Design of Alumni and Career Development Center Web Based Application Using Agile SDLC Methodology - Maulana, Bagoes; Siregar, Rosma; Hutahaean, Harvei Desmon; Sinaga, Tonggo (Bahasa Indonesia, 2023)
One of the primary benchmarks for evaluating the quality of higher education is the successful integration of its graduates into the workforce. Unfortunately, the Faculty of Engineering at Universitas Negeri Medan lacks a dedicated platform to facilitate the dissemination of job opportunities to its alumni and establish partnerships with employers to streamline this process. As a solution, this research endeavors to develop a web-based Alumni and Career Development Center application that serves as a bridge between the corporate sector and the industrial world, enabling alumni to access job opportunities and employers to connect online. The system design incorporates the Agile Method, UML, PHP programming language, and the MySQL database engine. However, there is still room for enhancement, particularly in integrating the candidate selection process. The testing data demonstrates promising results, underscoring the system's reliability for future implementation. The application has undergone testing and assessment, including an acceptability test with a rating of 88.32, falling within the valid range, and a user interface evaluation yielding a score of 0.916667, indicating a very high level of quality.